The effect of pH modification on wetting kinetics of a naturally water‐repellent coniferous forest soil. (4th April 2017) - Amer, A.; Schaumann, G. E.; Diehl, D.
Abstract : The interfacial dynamics of soil–water interactions are greatly affected by the hydrophobic properties of organic matter. The causes and underlying mechanisms responsible for the development of soil water repellency (SWR) are still under discussion. Various environmental factors control the appearance and degree of SWR. In addition to water content and temperature, the wetting of soil depends greatly on the physicochemical characteristics of soil surfaces, which in turn depend on pH. In this contribution, we propose a reaction mechanism for the change in SWR that is observed when soil pH is changed. Wetting kinetics were studied by time‐dependent sessile drop measurements (TISED) of the contact angle, the work of spreading and the diameter of the base of the drop as time elapsed under controlled relative humidity. Modification of pH strongly affected the wetting kinetics, suggesting maximum resistance to wetting at the control pH (3.6), with decreased resistance to wetting as pH was changed in either direction. The enhancement in wetting kinetics by the modification of soil pH can be attributed to the chemical modification in organic materials that coat the soil particles. This conclusion is based on the magnitude of activation energy associated with the spreading process. The combined effect of pH and temperature on the wetting kinetics, together with the compensation effect seen between the logarithmic pre‐exponential factor and activation energy, suggests acid–base catalysed hydrolysis–condensation reactions are the dominant processes responsible for the chemical nature of SWR. Highlights: How does the modification of pH affect soil wetting mechanisms? The dynamic sessile drop method was used to measure the wetting activation energy. Modification of soil pH decreases resistance to wetting and increases activation energy of wetting. Acid or base catalysed hydrolysis reactions increase chemical sorption sites for water molecules in soil.